Reliability, validity assessment of subjective norms dimension and its influence on intention to pay zakat - Muhammad, Sani Adamu; Saad, Ram Al Jaffri (Institut Pengurusan Kualiti (IPQ), 2016)
Payment of zakat via zakat institutions nowadays is the choice of zakat payer to pay or not to the institution or pay directly to asnaf.Survival of zakat institution solely depends on the level of funds collected from zakat payers.This collection will only increase if zakat institution understands the predictors of intention to pay zakat. Thus, the present study aims at examining the dimension of subjective norm’s reliability and validity on its relationship with intention to pay zakat in Kano Nigeria. The study found that items of the influence of religious leaders, items of peer influence are reliable and valid.Therefore, it is recommended they can be used in the main study in the field of zakat and related areas.